2013
DOI: 10.1055/s-0033-1352504
|View full text |Cite
|
Sign up to set email alerts
|

Laryngopharyngeal Reflux: Diagnosis, Treatment, and Latest Research

Abstract: Introduction Laryngopharyngeal reflux (LPR) is a highly prevalent disease and commonly encountered in the otolaryngologist's office. Objective To review the literature on the diagnosis and treatment of LPR. Data Synthesis LPR is associated with symptoms of laryngeal irritation such as throat clearing, coughing, and hoarseness. The main diagnostic methods currently used are laryngoscopy and pH monitoring. The most common laryngoscopic signs are redness and swelling of the throat. However, these findings are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…About 4−10% of patients who complain about laryngeal diseases are diagnosed with LPR [8]. Patients with reflux have the impaired physiological barriers that protect from acid gastric contents (upper and lower sphincter of the oesophagus, oesophageal mucosa, peristalsis, as well as saliva and gravity), acid gastric contents damage epithelium of the larynx and pharynx [9]. It was found that approximately half of patients with recurring laryngitis or voice disorders suffer from LPR.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…About 4−10% of patients who complain about laryngeal diseases are diagnosed with LPR [8]. Patients with reflux have the impaired physiological barriers that protect from acid gastric contents (upper and lower sphincter of the oesophagus, oesophageal mucosa, peristalsis, as well as saliva and gravity), acid gastric contents damage epithelium of the larynx and pharynx [9]. It was found that approximately half of patients with recurring laryngitis or voice disorders suffer from LPR.…”
Section: Discussionmentioning
confidence: 99%
“…A crucial examination in diagnostics of laryngopharyngeal reflux is also laryngoscopy, which shows changes in the larynx such as reddening, oedema or inflammation [7,9]. When the symptoms are intensive and persist for a long time, laryngoscopy is necessary to exclude other laryngeal diseases, including neoplasm [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations